Visualization through Magnetic Resonance Imaging of DNA Internalized Following “In Vivo” Electroporation - Simonetta Geninatti Crich; Stefania Lanzardo; Alessandro Barge; Giovanna Esposito; Lorenzo Tei; Guido Forni; Silvio Aime (Molecular Imaging)
The ability to visualize plasmid DNA entrapment in muscle cells undergoing an “in vivo” electroporation treatment was investigated on BALB/c mice using a 7-T magnetic resonance imaging (MRI) scanner using the paramagnetic Gd–DOTA–spd complex as imaging reporter. Gd–DOTA–spd bears a tripositively charged spermidine residue that yields a strong binding affinity toward the negatively charged DNA chain (6.4 kb, K a = 2.2 × 10 3 M −1 for approximately 2500 ± 500 binding sites). Cellular colocalization of Gd-DOTA-spd and plasmid DNA has been validated by histological analysis of excised treated muscle. In vivo MRI visualization of Gd-DOTA-spd distribution provides an excellent route to access the cellular entrapment of plasmid DNA upon applying an electroporation pulse.